A novel approach for modelling fluid flow and heat transfer in an Open Volumetric Air Receiver using ANSYS-FLUENT - Sharma P.; Chandra L.; Ghoshdastidar P.S.; Shekhar R. (My University, 2025)
Open volumetric air receiver (OVAR) has great potential as a source of process heat for metals processing operations. The two major components of OVAR are the porous absorbers and the return air flow chamber (RAFC). Heat exchange between the “cooler” return air and the hot curved absorber surface in RAFC is critical as it prevents overheating of absorbers. Unfortunately, modeling of air flow in the RAFC is conspicuous by its absence. Calculations were performed in ANSYS-FLUENT using the local thermal non-equilibrium model for heat transfer in the porous absorber. Three dimensional flow and heat transfer simulations were carried out in the RAFC. Unfortunately, ANSYS decoupled heat exchange between the absorbers and return air by splitting the curved absorber surface into real and imaginary surfaces. Decoupling also meant that heat flux had to be specified separately on the absorber and the RAFC, which was a challenge since only the total input solar flux is known. Hence the major contribution of this paper has been to incorporate two innovations in the simulation methodology. One, to couple the absorber and RAFC thermally by mapping the temperature of the real surface to the imaginary surface. Two, the flux used for heating air in the absorber was calculated iteratively. Limited simulations suggest that in laboratory experiments, relatively inexpensive circumferential (Joule) heating of absorbers can reasonably mimic heating of absorbers by concentrated solar radiation. © 2020 International Solar Energy Society